The Effect of Fermentation Lemna (Leman minor) Powder Raw Material for Feed Growth Rate, Feed Efficiency and Survival Rate of Red Tilapia (Oreochromis niloticus) - Yessi A. P. Manganang; Ely J. Karimela (Jurnal Biologi Tropis, 2023)
Feed is an important component in fish farming. The availability of local raw materials as an alternative material for making feed is very important to replace flour which is expensive. one of them is by utilizing fermented lemna flour as the main ingredient in making vegetable feed. With the fermentation process in raw materials, it can increase digestibility, storage capacity and increase the nutritional value of food and break down indigestible materials such as cellulose and hemicellulose into simple sugars. This study aims to determine the growth rate, efficiency of use of apakn and survival rate for red tilapia by feeding fermented lemna flour. The fish used in this research is red tilapia with a size of 3-5 cm and kept for 30 days. Ad libitum feeding. Treatment of fermented lemna flour consisted of 3 treatments : treatment A (without fermented lemna flour), B (fermented lemna flour 5%) and C (fermented lemna flour 10%). The data observed were  growth rate (RGR), feed  efficiency (EPP) and survival rate. The results showed that treatment C gave the best average value at RGR of 0.00677% / day, EPP of 0.00682% and survival rate of 100%.